Artificial Interphase Layer for Stabilized Zn Anodes: Progress and Prospects. Issue 40 (22nd August 2022) - Zhang, Qihui; Su, Yiwen; Shi, Zixiong; Yang, Xianzhong; Sun, Jingyu
Abstract: The burgeoning Li‐ion battery is regarded as a powerful energy storage system by virtue of its high energy density. However, inescapable issues concerning safety and cost aspects retard its prospect in certain application scenarios. Accordingly, strenuous efforts have been devoted to the development of the emerging aqueous Zn‐ion battery (AZIB) as an alternative to inflammable organic batteries. In particular, the instability from the anode side severely impedes the commercialization of AZIB. Constructing an artificial interphase layer (AIL) has been widely employed as an effective strategy to stabilize the Zn anode. This review specializes in the state‐of‐the‐art of AIL design for Zn anode protection, encompassing the preparation methods, mechanism investigations, and device performances based on the classification of functional materials. To begin with, the origins of Zn instability are interpreted from the perspective of electrical field, mass transfer, and nucleation process, followed by a comprehensive summary with respect to functions of AIL and its designing criteria. In the end, current challenges and future outlooks based upon theoretical and experimental considerations are included. Abstract : The instability issue of Zn anode greatly impedes the practicability of aqueous Zn‐ion batteries. Constructing an artificial interphase layer (AIL) serves as an effective strategy to stabilize the Zn anode. This review summarizes the recent advance in AIL design. Current challenges and future perspectives for realizing high‐performance Zn anode are also included.